Analisis Risiko Investasi Deposito Mudharabah (Studi pada Bank Syariah Mandiri Tahun 2013-2015) - Ulul Azmi Mustofa; Iin Emy Prastiwi (ITB AAS INDONESIA Surakarta, 2016)
Value at Risk is defined as an estimate of the maximum loss of an investment over a given period and a given confidence level. The purposes of this research is to understand the size of financial risk and net return of mudharabah deposit on Islamic bank using Value at Risk (VaR) approach. Objects of this research is quarterly financial report of Bank Syariah Mandiri, for three years, 2013-2015. VaR analysis shows that investment mudaraba deposits at Bank Syariah Mandiri as measured by VaR approach to investment risk (VaRmean) in 2013 amounted to 0.30%, and a net return of 0.54%, in 2014 the mean VaR 0.18%, and the net return 0.62%, in 2015 the mean VaR of 0.25%, and a net return of 0.55%. Keywords : Value at Risk ( VaR ), risk, net return, mudharabah deposit